A History of Bock Burst Research in the Coeur D'Alene Mining District - Michael Jenkins (International Conference on Ground Control in Mining, 1987)
This paper reviews the history of rock burst research in the Coeur d'Alene Mining District of northern Idaho over the last 30 years. Rock bursting is a problem because of a combination of geological factors in the region--complex structure, high horizontal stresses, and strong, brittle rock that readily stores strain energy. The Bureau of Mines has cooperated with industry to study rock burst phenomenon for many years. Early work focused on methods to mitigate bursting problems within the context of existing mining methods. In the 1970's, researchers began investigating methods for altering or controlling conditions that lead to rock bursts. These control measures become part of the stope development that precedes mining or are changes in the mining process itself. Although, researchers continue to develop microseismic techniques, the major research effort focuses on developing a new mining method to reduce the number and severity of rock bursts in order to improve safety and increase productivity in the Coeur d'Alene Mining District.